Alliance Motives among Manufacturing SMES: Evidence from an Emerging Economy - Muthoka, Richard K.; Kilika, James M.; Muathe, Stephen M. A. (European Scientific Journal, ESJ, 2022)
This study was designed to investigate the effect of environmental-based motives on firm performance. The study targeted manufacturing Small and Medium Enterprises based in Kenya whose performance has been negatively affected by high industry competition, low technology uptake, and industry regulation. The study was geared towards establishing the environmental-based motives pushing and pulling manufacturing Small and Medium Enterprises toward strategic alliance formation. To this end, the study was set to investigate whether compliance with government regulation, the need to grow market share, and the need to increase customer base motivates manufacturing Small and Medium Enterprises in Kenya to form strategic alliances. The target population for the study consisted of 74 SMEs and the study adopted descriptive and explanatory research designs and collected data from company CEOs or senior managers. Descriptive and inferential statistics were used to analyze the survey data. The study findings indicated that environmental-based motives have a positive and significant effect on the performance of manufacturing Small and Medium Enterprises in Kenya (Adj R2 = 0.484). Based on these findings, the study concluded that environmental-based motives of compliance with the government regulation, market share, and customer base motivate manufacturing Small and Medium Enterprises to form strategic alliances and that these motives have a positive and significant effect on firm performance. The study contributed to the general body of knowledge by bridging the contextual and empirical gaps identified after the literature review. The study recommends that top management teams in the manufacturing industry should map environmental-based motives and align such motives to specific aspects of their value chain activities.